Discordant Post-natal Patterns in Fetuses With Heterotaxy Syndrome: A Retrospective Single-Centre Series on Outcome After Fetal Diagnosis - Seidl-Mlczoch, Elisabeth; Kasprian, Gregor; Kitzmueller, Erwin; Zimpfer, Daniel; Steiner, Irene; Jowett, Victoria; Stuempflen, Marlene; Wielandner, Alice; Ulm, Barbara; Michel-Behnke, Ina (Frontiers in Pediatrics, 2022)
Objective Cardiac and extra-cardiac anomalies in 46 pre-natally diagnosed cases of heterotaxy were compared to post-natal anatomical patterns in order to reveal discordant findings. Second, the outcome of these fetuses was evaluated. Methods Fetuses with heterotaxy, diagnosed in a tertiary referral centre, were analysed retrospectively. Based on the foetal abdominal situs view, right atrial isomerism (RAI) and left atrial isomerism (LAI) were defined as foetal sub-types. Post-natally, discordant anatomical patterns for broncho-pulmonary branching, atrial appendage morphology, and splenic status were further clarified with CT scans. In summary, the spectrum of pre-natally and post-natally detected cardiac and extra-cardiac anomalies is systematically reviewed. Necessary surgical interventions and mid-long-term outcomes were compared between the two sub-types in surviving infants. Results A total of 46 fetuses with heterotaxy were included; LAI was diagnosed in 29 (63%) fetuses and RAI was diagnosed in 17 (37%) fetuses. Extra-cardiac anomalies were noted in 35% of fetuses. Seven out of the 29 fetuses (24%) with LAI had atrio-ventricular block (AVB) and four of these cases presented with hydrops. Twenty nine out of the 46 participating fetuses (63%) were live births, with 62% in the LAI group and 65% in the RAI group. Five fetuses were lost to follow-up. At the age of 1 year, the overall survival of live births [estimate (95% CI)] was 67% (48; 92%) in patients with LAI and 55% (32; 94%) in patients with RAI. At the age of 5 years, the estimates were 67% (48; 92%) in the LAI group and 46% (24–87%) in the RAI group. The median survival (first quartile; third quartile) was 11.1 (0.1; 14) years for patients with LAI and 1.3 (0.09; NA) years for patients with RAI. Of 17 children who had undergone cardiac surgery, five (29%) children achieved a bi-ventricular repair and 12 (70%) children achieved a uni-ventricular palliation. Three were primarily palliated, but converted to bi-ventricular thereafter. Foetal subtype definition of heterotaxy based on the abdominal situs and post-natal thoracic imaging studies showed a discordant pattern of broncho-pulmonary branching and atrial appendage anatomy in 40% of our live-born children. Conclusion Heterotaxy is a rare and complex condition with significant morbidity and mortality related to severe cardiac and extra-cardiac associations. Accurate pre-natal diagnosis can help identify the fetuses at risk and allow for timely intervention in a multi-disciplinary setting. Further studies are warranted to shed light on the exact sub-type definition in fetuses with heterotaxy and the presence of discordant post-natal patterns.